Phytochemical, Antioxidant and Antimicrobial Evaluation of Nigerian Kalanchoe pinnata (Lam.) Roots - Kendeson, Christiana; Kagoro , Mary L.; Adelakun, Esther A. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2024)
Background: Kalanchoe pinnata (Lam.) is a plant belonging to the family Crassulaceae or orpine family and reported to possess medicinal properties. This study was undertaken to investigate the phytochemical profile, as well as the antioxidant and antimicrobial properties of the Nigerian Kalanchoe pinnata (Lam.) root extract. Methods: The roots of the plant (300 g) were extracted with 70 % ethanol. The quantitative and qualitative phytochemical screening was done following standard methods. The antioxidant activity was determined by evaluating the scavenging activity using DPPH (1,1-diphenyl-2-picryl hydrazyl) radical assay and the antimicrobial activity was determined using the agar well diffusion method. Results: The percentage yield of the extract was found to be 3.79 %. From the phytochemical screening alkaloids, flavonoids, glycosides, phenolics, saponins, steroids/terpenes and tannins were detected. The quantitative analysis gave the phenolic content as 3.800 ± 0.023 mg gallic acid equivalent; flavonoid content as 0.277 ± 0.004 mg quercetin equivalent and tannin content as 0.017 ± 0.057 mg tannic acid equivalent. The antioxidant assay result indicated that the plant exhibited antioxidant activity with IC50 value of 40.56 and 35.47 µg/mL for ascorbic acid and root extract respectively. The antimicrobial activity results showed that the crude extract inhibited the growth of test microorganisms Bacillus cereus, Echerichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumoniae, Aspergillus niger and Candida albicans; the extract was inactive against Salmonella typhi. Conclusion: These findings indicate that the plant possesses antioxidant and antimicrobial properties